2002
DOI: 10.1111/1468-0009.00019
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Health Development: An Integrated Framework for Developing Health, Policy, and Research

Abstract: T his article describes the Life Course Health Development (LCHD) framework, which was created to explain how health trajectories develop over an individual's lifetime and how this knowledge can guide new approaches to policy and research. Using recent research from the fields of public health, medicine, human development, and social sciences, the LCHD framework shows that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
565
0
16

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 794 publications
(590 citation statements)
references
References 132 publications
9
565
0
16
Order By: Relevance
“…A vast amount of empirical literature investigating the developmental, genomic, and epigenetic origins of health and disease -as well as on the epidemiology of chronic disease across the life course -has been generated in the past two decades (Halfon and Hochstein 2002;Kuh and Ben-Shlomo 2004;Gluckman and Hanson 2004;Gluckman et al 2008;Kuh et al 2013;Berkman et al 2014;Halfon et al 2014; the evolution of life course health science is reviewed in Perhaps the biggest stimulus for thinking differently about origins and development of chronic disease came from a series of provocative studies that were conducted by David Barker and his team. Beginning in the 1980s, Barker's studies began to describe how the prevalence of heart disease in specific areas of England was related to the distribution of birth weights in those same regions.…”
Section: The Maturation Of the Lchd Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…A vast amount of empirical literature investigating the developmental, genomic, and epigenetic origins of health and disease -as well as on the epidemiology of chronic disease across the life course -has been generated in the past two decades (Halfon and Hochstein 2002;Kuh and Ben-Shlomo 2004;Gluckman and Hanson 2004;Gluckman et al 2008;Kuh et al 2013;Berkman et al 2014;Halfon et al 2014; the evolution of life course health science is reviewed in Perhaps the biggest stimulus for thinking differently about origins and development of chronic disease came from a series of provocative studies that were conducted by David Barker and his team. Beginning in the 1980s, Barker's studies began to describe how the prevalence of heart disease in specific areas of England was related to the distribution of birth weights in those same regions.…”
Section: The Maturation Of the Lchd Fieldmentioning
confidence: 99%
“…They also suggested that some general principles were emerging and beginning to outline a new model or framework that they termed "life course health development." At the same time, many other scientists provided their own synthesis of this emerging literature and what they considered to be its implications for health, health-care delivery, and health policy (Ben-Shlomo and Kuh 2002;Halfon and Hochstein 2002;Lu and Halfon 2003;Forrest and Riley 2004;Worthman and Kuzara 2005). These various attempts at synthesizing the evidence from this new field constituted a tipping point, and over the next decade, the number of empirical studies accelerated at a much faster pace as the early objections to the "Barker hypothesis" melted away in the wake of many confirmatory studies, and the explanatory power of this new conceptualization began to take hold.…”
Section: The Maturation Of the Lchd Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…9 questionnaires or interviews. But development of health behaviors and health risks over the life course (Halfon andHochstein, 2002 andKrieger, 2005) and behavior change and adaptation are processes that unfold over time; advancing knowledge about these critical health processes requires information obtained from repeated measures or longitudinal studies. Yet, few studies in nursing are based on longitudinal data (Henly, Wyman, & Findorff, 2011) or take advantage of models for longitudinal data that are now standard in the behavioral sciences (e.g., Hedeker and Gibbons, 2006, Singer and Willett, 2003and Skrondal and Rabe-Hesketh, 2004.…”
Section: Health Behavior Behavior Change and Biobehavioral Nursingmentioning
confidence: 99%
“…Unaddressed developmental problems and poor childhood health have important implications for future health and wellbeing [1][2][3]. Effective screening and early identification of developmental delays through primary healthcare services, however, continues to be a challenge given that less than a third of pediatric providers screen with a structured, validated developmental tool and many children with developmental problems are not identified until school age [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%